Partisipasi Masyarakat dalam Pembuatan Kebijakan Perlindungan Whistleblower melalui Teknologi Blockchain Di Indonesia: Pendekatan Transparansi dan Akuntabilitas - Alena, Kayla Putri; Hadinugroho, Dwi Septian; Kusmana, Daffa Meazza; Nufus, Naufal Rafi; Fatkhuri, Fatkhuri (Journal of Social Contemplativa, 2025)
Whistleblower protection in Indonesia remains a critical issue due to inadequate security guarantees, anonymity concerns, and weak regulatory implementation. Blockchain technology offers an innovative solution by ensuring secure, decentralized data recording while preserving whistleblower anonymity. This approach enhances transparency and accountability in reporting systems. Community participation is equally essential to develop inclusive and legitimate policies. However, challenges such as digital disparities, low technological literacy, and insufficient infrastructure hinder blockchain adoption in Indonesia. Collaborative efforts between the government, society, and related institutions are crucial to establishing an effective whistleblower protection system. The integration of modern technology and participatory approaches has the potential to strengthen